Lessons learned from the integration of Strategic Environmental Assessment with transport planning in Athens, Dublin and London - Zagorianakos, Efthimis I. (Trinity College (Dublin, Ireland). Department of Zoology, 2001)
Strategic Environmental Assessment (SEA) refers to the identification and evaluation of the positive and negative effects of actions at a higher decision making level than development projects such as programmes, plans and policies (PPPs). Its usefulness lies in its ability to aid decision making, enhance the effectiveness of project environmental assessment and ultimately contribute towards Sustainable Development. It is for these characteristics that the concept is currently the subject of a European Union draft Directive 'on the assessment of the effects of certain plans and programmes on the environment' [96/0304 (COD)] or SEA Directive.
Keywords: Environmental Science, Ph.D.; Ph.D. Trinity College Dublin